Outcome of penile lengthening of adolescents and young adults born with bladder exstrophy and epispadias. Issue 3 (June 2021) - Fainberg, Jonathan; Gamal, Ashraf; Hanna, Moneer K.
Summary: Background: The decreased penile length in patients born with BE results partly from pubic symphysis diastasis and the separation of the corporal bodies, which causes a shortened penis as the corporal length is lost in traversing the distance between the pubic rami. However, in some cases there is an intrinsic penile abnormality and dorsal chordee. Furthermore, multiple surgeries has in some cases, resulted in cutaneous and subcutaneous scarring, which contributed to the problem of the short phallus and dorsal tethering to the abdominal wall (figure). Objective: Herein we evaluated the outcome of penile lengthening, repair of penile upward tethering to the abdominal wall and dorsal curvature in males born with bladder exstrophy and epispadias (BEE). Study design: We reviewed the records of 34 patients (11–29 years old) born with BE (31pts.) and epispadias (3 pts.). The parents and/or the young men were referred because of their dissatisfaction with and complains of short penile length, and upward tethering/chordee. The penile lengthening was achieved by detaching the corporal bodies from the pubic rami and suturing the corporal bodies as reported by Johnston (figure) However, in 11 patients who had had multiple surgeries the periosteum was incised and the corporal dissection was performed subperiosteally to protect the erectile tissues. In 16 pts dermal grafts of the dorsal corporal wall was performed to correct the dorsal curvature. 13 patients underwent single stage augmentation urethroplasty. Results: Surgical complications were encountered in 4 pts (11.7%). Subjective evaluation by the patient and/or parents reported satisfactory and/or very satisfactory results in 31/34 (91%). The degree of penile lengthening measured at 6 months and one year postoperatively showed increased length which varied between 50% and 150% of the preoperative penile length. Conclusions: As children born with BEE transition to adolescence and adulthood, the external genitalia acquire greater importance. The short phallus and/or dorsal chordee and/or upwards tethering can be corrected successfully in the majority of patients. Summary Figure Summary Figure